Expressed support, perceived support and physical ability in chronic pain patients. - Patrick, Louise. (University of Ottawa (Canada), 1992)
This study investigated the relationship between social support within the marital context, and physical ability in chronic pain patients. Fifty patients diagnosed with chronic pain and their spouses participated in the study. Each patient was asked to exercise on a stationary bicycle, with his/her spouse present. The interactions between patient and spouse were videorecorded and the spouse's behaviour was rated for the amount of task-related and emotional support expressed. The relationships among the spouse's behaviour, the patient's perception of that behaviour and the patient's physical ability were examined. Marital adjustment, depressive symptomatology and the spouse's perception of the patient's physical limitations were investigated as predictors of expressed and perceived support. Zero-order correlations replicated the previously demonstrated positive relationships among the patient's report of spouse support, pain intensity and marital adjustment. Using hierarchical regression to control for the patient's depressive symptomatology and marital adjustment, it was found that observed spouse support was positively related to the patient's physical ability, accounting for 13% of the variance. When pain severity was also entered into the equation, results indicated that pain intensity was the only significant predictor and was negatively related to the patient's physical ability, accounting for 43% of the variance. No significant predictor of the spouse's expressed support was identified, while the patient's marital adjustment was positively related to his/her perception of support. Descriptive reports by patients of their perception of support during the physical ability task indicated that patients experienced task and emotional support differently. The majority of patients reported that emotional support was experienced as supportive and helpful, but task-related support was not.
Keywords: Psychology, Clinical.